Diagnostic Implication of Mean Platelet Volume in Thrombocytopenia - Bhat, Archana; Goveas, Christina; S, Jayaprakash C (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: The newer haematology analysers measure the platelet indices such as the mean platelet volume (MPV), platelet large cell ratio and platelet distribution width. It has been observed that MPV is increased in conditions associated with thrombocytopenia due to peripheral destruction. This study was carried out to know the utility of MPV and derive cut-off values in categorizing the conditions causing thrombocytopenia into hyperdestructive and hypoproliferative groups. Methods: The thrombocytopenia cases were categorized into two groups as hyperdestructive and hypoproliferative groups based on the bone marrow findings. The MPV on the day of admission was taken into consideration. The data were analysed using the mean, standard deviation and the t-test. ROC curve was plotted to derive the cut-off MPV value. Results: Of the total 89 thrombocytopenia cases, 53 were of hyperdestructive etiology and 36 were of hypoproliferative etiology. The mean MPV for group A was 9.56 with a standard deviation of 1.34 and that for group B was 8.45 with a standard deviation of 1.30. The p value was < 0.001. From the ROC curve, a cut off of 8.5 fl was taken. Conclusion: We conclude that a MPV value of >8.5fl is suggestive of a hyperdestructive etiology. Even though bone marrow remains a gold standard to distinguish between the hyperdestructive and hypoproductive thrombocytopenia groups, platelet indices like MPV can be used to aid in the diagnosis of etiology of thrombocytopenia.